2018
DOI: 10.7567/jjap.57.114201
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of Hf-based metal/oxide/nitride/oxide/silicon structure for nonvolatile memory application

Abstract: In this study, we investigated the electrical characteristics of a Hf-based metal/oxide/nitride/oxide/silicon (MONOS) nonvolatile memory (NVM) device formed in situ for the first time. Furthermore, the effects of the in situ HfN gate stack formation process on the electrical characteristics of the Hf-based MONOS device were also investigated by comparing with the device with the Al gate formed ex situ. The drain-current–gate-voltage (ID–VG) characteristics with negligible hysteresis and high yield were realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…9) This process would cause the degradation of interface characteristics because of the contamination at each interface of the MONOS structure during the transfer of the wafers, and it would lead to the degradation of device characteristics. 10) To achieve low-voltage operation for MONOS NVM devices, a MONOS structure with excellent interface property is necessary.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9) This process would cause the degradation of interface characteristics because of the contamination at each interface of the MONOS structure during the transfer of the wafers, and it would lead to the degradation of device characteristics. 10) To achieve low-voltage operation for MONOS NVM devices, a MONOS structure with excellent interface property is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have reported the excellent electrical characteristics of a Hf-based MONOS structure formed in situ by ECR plasma sputtering with a HfO 2 and HfON tunneling layer (TL). 10,[14][15][16][17][18][19][20][21] The composition of each layer was reported, and it is designed using the reported results, previously. 10) In the case of HfO 2 , the SiO 2 interfacial layer (IL) is formed between the TL and Si substrate which increased the equivalent oxide thickness (EOT) and degraded operation speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] We have reported the Hf-based MONOS NVM with high-k HfO 2 and HfN 1.1 dielectrics. [11][12][13][14][15][16][17] The Hf-based MONOS structures were fully in situ formed to improve the interface property by the reactive sputtering utilizing Hf target. The MONOS structures are consisted from HfN 0.5 gate electrode, HfO 2 blocking layer (BL), HfN 1.1 charge trapping layer (CTL), HfO 2 tunneling layer (TL), and we have demonstrated the multibit/cell operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the threshold voltage (V TH ) controllability was necessary to be improved. 15) The possible method to improve the MONOS characteristics is the use of high-k multi CTL. Tang et al reported that the multi CTL formed by the multi Zr silicate layers to improve the MONOS characteristics.…”
Section: Introductionmentioning
confidence: 99%